Manajemen Pendidikan Islam Berbasis Karakter di Pondok Pesantren Islahuddini Kediri Lombok Barat - Badrun, Badrun (Jayapangus Press, 2024)
This research aims to explore and analyze the implementation of character-based Islamic education management at the Islahuddin Islamic Boarding School in Kediri and its impact on the formation of the morals and character of the students. The research method used is qualitative research with a descriptive analytical approach. Data was collected through participant observation, in-depth interviews, and document analysis. The results of the research show that the Islahuddin Kediri Islamic Boarding School has succeeded in implementing character-based Islamic education management through structured and integrated programs, including the habituation of Islamic values in daily activities, personality development, and the cultivation of noble character. The impact of this implementation can be seen in increasing moral awareness, responsible attitudes and high social awareness among students. These findings provide an important contribution in the development of character-based Islamic education management models in other Islamic educational institutions.